Impact of dietary fatty acids on metabolic activity and host intestinal microbiota composition in C57BL/6J mice. Issue 11 (14th June 2014) - Patterson, Elaine; O' Doherty, Robert M.; Murphy, Eileen F.; Wall, Rebecca; O' Sullivan, Orla; Nilaweera, Kanishka; Fitzgerald, Gerald F.; Cotter, Paul D.; Ross, R. Paul; Stanton, Catherine
<x content-type="archive" xml:space="preserve">Abstract</x> Different dietary fat and energy subtypes have an impact on both the metabolic health and the intestinal microbiota population of the host. The present study assessed the impact of dietary fat quality, with a focus on dietary fatty acid compositions of varying saturation, on the metabolic health status and the intestinal microbiota composition of the host. C57BL/6J mice (n 9–10 mice per group) were fed high-fat (HF) diets containing either (1) palm oil, (2) olive oil, (3) safflower oil or (4) flaxseed/fish oil for 16 weeks and compared with mice fed low-fat (LF) diets supplemented with either high maize starch or high sucrose. Tissue fatty acid compositions were assessed by GLC, and the impact of the diet on host intestinal microbiota populations was investigated using high-throughput 16S rRNA sequencing. Compositional sequencing analysis revealed that dietary palm oil supplementation resulted in significantly lower populations of Bacteroidetes at the phylum level compared with dietary olive oil supplementation (P< 0·05). Dietary supplementation with olive oil was associated with an increase in the population of the family Bacteroidaceae compared with dietary supplementation of palm oil, flaxseed/fish oil and high sucrose (P< 0·05). Ingestion of the HF-flaxseed/fish oil diet for 16 weeks led to significantly increased tissue concentrations of EPA, docosapentaenoic acid and DHA compared with ingestion of all the other diets (P< 0·05); furthermore, the diet significantly increased the intestinal population of Bifidobacterium at the genus level compared with the LF-high-maize starch diet (P< 0·05). These data indicate that both the quantity and quality of fat have an impact on host physiology with further downstream alterations to the intestinal microbiota population, with a HF diet supplemented with flaxseed/fish oil positively shaping the host microbial ecosystem.